Pengaruh Konsentrasi Kepemilikan, Ukuran Perusahaan, Asimetri Informasi, Leverage, Dan Corporate Governance Terhadap Manajemen Laba (Studi Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Pada Tahun 2013-2015) - Rachmawati, Erma, Dr. Erma Setiawati, MM, CA (2017)
The study aims to analyze the effect of concentration of ownership, company size, asymmetri of information, leverage, and corporate governance on earnings management in Manufacturing companies. Corporate governance is measured by boards size commissioners, institutional ownership, managerial ownership, and audit committees. The sample which used in this research is 162 manufacturing companies which listed in Indonesian Stock Exchange on 2013-2015. The sampling method used in this research is purposive sampling method. The method of analysis used in this study is multiple regression analysis. Based on the result of analysis conclude that concentration of ownership, leverage, boards size commissioners, institutional wnership, and audit committees have no significant effecton earnings management. Meanwhile company size, asymmetry of information, and managerial ownership has a positive effecton earnings management.